Does Monetary Policy Influence Euro Area Fiscal Sustainability? - António Afonso; Francisco Gomes-Pereira (CESifo GmbH, 2024)
This paper studies the impact of monetary policy on fiscal sustainability in the euro area. Our sample includes 12 euro area countries and covers the period from 2003:Q1 to 2022:Q4. We extend a fiscal reaction function (Bohn's rule) by including the monetary policy stance as an interaction term. Our findings are as follows: First, a contractionary (expansionary) monetary stance tends to lead to an increase (decrease) in the primary balance. Second, the ECB's monetary policy stance significantly influences the fiscal reaction function coefficient. In other words, contractionary monetary policy induces a larger increase in primary balances in response to an increase in the debt-to-GDP ratio than if monetary policy was neutral or expansionary. Our findings suggest that expansionary monetary policy has the potential to help fiscal sustainability, and potentially mitigate fiscal fatigue. Conversely, contractionary monetary policy can exacerbate the fiscal effort required to satisfy the government intertemporal budget constraint.
Keywords: E52; E58; E63; 330; monetary policy stance; fiscal sustainability; debt sustainability